VO2@PDMA nanoparticles, preparation method and intelligent thermal insulation coating made therefrom

By preparing VO2@PDMA nanoparticles, the bi-shell structure is used to improve the stability and dispersion of VO2 and enhance compatibility with organic resin, the dispersion and stability of VO2 nanopowders in the aqueous system are solved. The problem is that efficient heat insulation effect and excellent weather resistance are achieved.

CN117025016BActive Publication Date: 2025-02-11UNIV OF JINAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310972806.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-11
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

In the prior art, the dispersion, poor stability, and insufficient compatibility with organic film-forming resins in the aqueous system, resulting in defects in the interface structure and oxidation problems.

Method used

By preparing VO2@PDMA nanoparticles, a bishell structure is adopted, in which the hydrophobic shell layer of the internal silane coupling agent improves the stability of VO2, and the external hydrophilic shell layer PDMA improves the dispersion of VO2 in the aqueous system and enhances the organic Compatibility of resin.

Benefits of technology

The excellent dispersion and stability of VO2 nanopowders in aqueous systems are achieved, the interface structure defects are reduced, the weather resistance of functional coatings is improved, and the near-infrared dimming performance and thermal insulation effect are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117025016B_ABST
    Figure CN117025016B_ABST
Patent Text Reader

Abstract

The present invention provides a VO2@PDMA nanoparticle, a preparation method and an intelligent thermal insulation coating prepared therefrom, belonging to the field of functional composite materials. The preparation method of the present invention comprises the following steps: (1) preparation of vanadium dioxide powder; (2) preparation of a thiol-terminated PDMA-SH hydrophilic polymer; (3) preparation of VO2@PDMA nanoparticles. The preparation method provided by the present invention is simple to operate, and the prepared VO2@PDMA nanoparticles have excellent stability, dispersibility and near-infrared dimming performance, and have great advantages in application in the field of coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional composite materials, and specifically relates to VO2@PDMA nanoparticles, a preparation method and an intelligent thermal insulation coating made therefrom. Background Art

[0002] Vanadium dioxide (VO2) is a thermochromic material that can undergo phase change at 68°C. When the temperature rises from room temperature to 68°C, the insulating phase of vanadium dioxide will transform into a metallic phase, accompanied by the change of infrared light from transmission to reflection. Taking advantage of the difference in infrared light reflectivity before and after the phase change, it can be used as a coating material to intelligently control the transmittance of near-infrared light in building doors and windows, thereby intelligently controlling indoor temperature and reducing the use of indoor air conditioning and cooling in high temperature environments, which is conducive to reducing energy consumption and achieving energy conservation and emission reduction. However, VO2 is easily oxidized to vanadium pentoxide (V2O5) by water, oxygen, etc. Therefore, in practical applications, VO2 has poor stability in water-based resins, and in the functional coating, due to the poor compatibility of VO2 and organic film-forming resins, there are structural defects at the interface between the two. Oxygen, water vapor, etc. at the interface will also cause oxidation of VO2 in the coating. Currently, the commonly used method to improve the stability of VO2 powder and its compatibility with organic resins is to use organic small molecules or inorganic oxides and other materials to coat VO2 nanopowders. The shell material forms a dense protective layer on the surface of the powder, thereby improving the stability of VO2 nanopowders.

[0003] While improving the stability of VO2 nanopowder, how to further improve its dispersibility in aqueous systems, its compatibility with organic film-forming resins and reduce interface structural defects remains a difficult problem that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to provide a VO2@PDMA nanoparticle, a preparation method and an intelligent thermal insulation coating prepared therefrom, which are used to solve the problems of poor dispersibility and poor stability existing in the current prior art.

[0005] In order to achieve the above purpose or other purposes, the present invention is implemented through the following technical solutions.

[0006] A method for preparing VO2@PDMA nanoparticles comprises the following steps:

[0007] (1) Preparation of vanadium dioxide powder; (2) Preparation of thiol-terminated PDMA-SH hydrophilic polymer; (3) Preparation of VO2@PDMA nanoparticles.

[0008] Specifically, the steps include:

[0009] (1) Preparation of vanadium dioxide powder:

[0010] Add V2O5 to deionized water, stir to form a dispersion, heat the dispersion and drop hydrazine hydrate under stirring, continue stirring to react after the dropwise addition is completed, then transfer the solution to a reactor to continue the reaction, perform post-treatment after the reaction is completed, and obtain vanadium dioxide powder;

[0011] (2) Preparation of thiol-terminated PDMA-SH hydrophilic polymer: a) N,N-dimethylacrylamide, S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) and azobisisobutyronitrile were added to 1,4-dioxane solvent, and stirred to react under nitrogen protection after being completely dissolved. After the reaction was completed, the resulting solution was precipitated and washed in n-hexane, and filtered. The resulting product was vacuum dried at 40-90° C. for 8-24 h to obtain trithioester-terminated poly(N,N-dimethylacrylamide), which was recorded as PDMA-DOPAT;

[0012] b) adding the PDMA-DOPAT, n-hexylamine and tributylphosphine prepared in step a) into tetrahydrofuran, stirring and reacting under nitrogen protection, and after the reaction, dropping the solution into n-hexane for precipitation and washing, collecting the precipitate by filtration, and vacuum drying at 40-90° C. for 8-24 h to obtain a thiol-terminated PDMA-SH hydrophilic polymer;

[0013] (3) Preparation of VO2@PDMA nanoparticles: The vanadium dioxide powder prepared in step (1) was ultrasonically dispersed in anhydrous ethanol, ammonia water was added to adjust the pH, γ-(methacryloyloxy)propyltrimethoxysilane was added, and the system was then heated for reaction. After the reaction, the system was centrifuged, washed with anhydrous ethanol, and vacuum dried at 40-70°C for 12-24h to obtain VO2@KH-570 nanopowder;

[0014] The VO2@KH-570 nanopowder is ultra-dispersed in tetrahydrofuran, and then the PDMA-SH hydrophilic polymer prepared in step (2) is added and stirred until fully dissolved, and then the initiator AIBN is added, and then reacted under nitrogen protection. After the reaction is completed, centrifugation and tetrahydrofuran washing are performed, and the washed product is vacuum dried at 50-70°C for 12-24h to obtain VO2@PDMA nanoparticles.

[0015] Preferably, in step (1), the mass ratio between V2O5 and deionized water is (1-5): (70-150).

[0016] Preferably, in step (1), the dispersion is heated to 50-80° C. and then hydrazine hydrate is added dropwise under stirring.

[0017] Preferably, in step (1), the mass ratio of V2O5 to hydrazine hydrate is (5-10): (1-5).

[0018] Furthermore, the selected hydrazine hydrate is 40wt% hydrazine hydrate.

[0019] Preferably, the hydrazine hydrate dropping speed in step (1) is 0.1 to 1 mL / min.

[0020] Preferably, after the dropwise addition in step (1) is completed, the stirring reaction time is continued for 0.5 to 5 hours. Preferably, in step (1), the reaction temperature in the reactor is 240 to 350° C., and the reaction time is 6 to 30 hours.

[0021] Preferably, after the reaction in step (1) is completed, the post-treatment sequentially comprises centrifugation at a speed of 1000-8000 rpm for 5-20 min and vacuum drying at 40-90° C. for 8-24 h.

[0022] Preferably, in step (2), the mass ratio of N,N-dimethylacrylamide (DMA) and S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT) in a) is (80-120):(5-15).

[0023] Preferably, in step (2), the mass ratio of S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT) and azobisisobutyronitrile (AIBN) in a) is (15-50): (0.5-7).

[0024] Preferably, in step (2), the mass ratio of 1,4-dioxane to N,N-dimethylacrylamide in a) is (5-10):(0.5-5).

[0025] Preferably, in step (2), the reaction temperature under nitrogen protection in a) is 50-70° C., and the reaction time is 6-24 h.

[0026] Preferably, in step (2), the mass ratio of PDMA-DOPAT, n-hexylamine and tributylphosphine in b) is (90-150):(10-30):(0.5-5).

[0027] Preferably, in step (2), the mass ratio of PDMA-DOPAT to tetrahydrofuran in step b) is 1:(5-30).

[0028] Preferably, in step (2), the stirring reaction temperature under nitrogen protection in step b) is 20 to 60° C.; and the stirring reaction time is 2 to 12 h.

[0029] Preferably, the ultrasonic dispersion time in step (3) is 10 to 40 minutes.

[0030] Preferably, in step (3), the mass ratio of vanadium dioxide powder to anhydrous ethanol is (0.1-4):(60-120).

[0031] Preferably, in step (3), aqueous ammonia is added dropwise to adjust the pH to 8-12.

[0032] Preferably, in step (3), the mass ratio of vanadium dioxide powder to γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) is (1-20): (0.2-1).

[0033] Preferably, the heating reaction temperature in step (3) is 50-70° C., and the reaction time is 3-10 h.

[0034] Preferably, in step (3), the unreacted KH-570 is removed by washing with anhydrous ethanol for 3 to 5 times.

[0035] Preferably, in step (3), the mass ratio of VO2@KH-570 nanopowder to tetrahydrofuran is (0.1-10): (60-120).

[0036] Preferably, in step (3), the mass ratio of VO2@KH-570 nanopowder to PDMA-SH hydrophilic polymer is (1-10): (0.5-2).

[0037] Preferably, in step (3), the mass ratio of VO2@KH-570 nanopowder to AIBN is (20-50):1.

[0038] Preferably, the reaction temperature under nitrogen conditions in step (3) is 50-70° C., and the reaction time is 12-24 h.

[0039] The present invention also protects VO2@PDMA nanoparticles prepared by the above method. The particle size of the VO2@PDMA nanoparticles is 30-40 nm.

[0040] The third aspect of the present invention also provides an intelligent thermal insulation coating prepared using the above-mentioned VO2@PDMA nanoparticles. The preparation method of the intelligent thermal insulation coating is: dropwise add the aqueous dispersion of VO2@PDMA nanoparticles into the aqueous resin, stir until uniformly dispersed, and obtain a system dispersion; mix the film-forming aid, leveling agent, and defoaming agent uniformly, and then add them to the system dispersion and stir evenly to obtain the intelligent thermal insulation coating.

[0041] Furthermore, the mass ratio of the aqueous resin to the VO2@PDMA nanoparticle aqueous dispersion is (50-100): (40-60); the mass fraction of the VO2@PDMA nanoparticle aqueous dispersion is 1 wt%.

[0042] Furthermore, the dripping speed of the aqueous dispersion of VO2@PDMA nanoparticles is 0.5-2 mL / min. Furthermore, the stirring rate during the dripping process is 500-2000 rpm, and the stirring time after the dripping is completed is 0.5-5 h.

[0043] Furthermore, the water-based resin is selected from water-based polyurethane resin and water-based acrylate resin.

[0044] Furthermore, the mass ratio of the water-based resin, the film-forming aid, the leveling agent, and the defoaming agent is (50-100): (10-30): (1-5): (1-5).

[0045] Furthermore, the film-forming aid is selected from alcohol ether film-forming aids, the leveling agent is selected from silicone leveling agents, and the defoaming agent is selected from silicone resin defoaming agents.

[0046] The smart heat-insulating coating prepared by the present invention is evenly coated on the surface of an ordinary clean glass plate by a conventional roller coating method, and the wet film thickness after coating is 45 to 55 μm, thereby obtaining smart heat-insulating glass. Specifically, the smart heat-insulating coating is evenly coated on the surface of a clean glass plate by a roller coating method, and is placed in an oven at 60° C. to assist the accelerated curing of the coating, thereby obtaining vanadium dioxide-based smart heat-insulating glass.

[0047] The VO2@PDMA nanoparticles provided by the present invention are a vanadium dioxide-based hybrid material with a double shell, which utilizes the hydrophobic shell of the internal silane coupling agent to improve the stability of the vanadium dioxide powder, while the external hydrophilic shell PDMA can improve the dispersibility of vanadium dioxide in the aqueous emulsion, and at the same time, the interfacial hydrogen bonds between the shell material and the film-forming resin help to improve the compatibility of the filler and the resin, reduce the interface structural defects inside the functional coating, and improve the weather resistance of the functional coating. The preparation method provided by the present invention is simple to operate, and the prepared VO2@PDMA nanoparticles have excellent stability, dispersibility and near-infrared dimming performance, and have great advantages in the field of coatings.

[0048] The intelligent thermal insulation coating prepared by the VO2@PDMA nanoparticles prepared in the present invention has excellent dimming performance and can achieve efficient thermal insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The H NMR spectrum of PDMA-DOPAT prepared in Example 1 (Avance III HD 600 MHz NMR spectrometer, deuterated acetone as solvent);

[0050] Figure 2 The UV absorption spectra of the PDMA-DOAPT polymer prepared in Example 1 before and after aminolysis (the solvent is tetrahydrofuran, the concentration of the polymer solution is 0.001 g / mL, and the UV-3600 UV-visible-near infrared spectrophotometer);

[0051] Figure 3 This is a scanning electron microscope image of the vanadium dioxide powder prepared in Example 1;

[0052] Figure 4 The thermal weight loss curves of vanadium dioxide powder, VO2@KH-570 nanoparticles, and VO2@PDMA nanoparticles prepared in Example 1 (TGA55 thermogravimetric analyzer tested the thermal weight loss of samples in a N2 atmosphere, the test temperature range was 30-700°C, and the heating rate was 20°C / min);

[0053] Figure 5 XRD patterns of vanadium dioxide powder and VO2@PDMA nanoparticles prepared in Example 1;

[0054] Figure 6 The dispersibility test of vanadium dioxide powder and VO2@PDMA nanoparticles prepared in Example 1 in water (0.1g VO2 and VO2@PDMA nanoparticles were dispersed in 8mL distilled water, and then ultrasonically dispersed for 30min using a cell crusher, and the sedimentation of the two was observed at rest);

[0055] Figure 7 Actual pictures of the smart thermal insulation coatings prepared in Application Example 1, Application Example 2, and Application Example 3 (a), and UV-visible-near-infrared transmission spectra at different temperatures (b) (the optical properties of the samples were tested by UV-visible-near-infrared spectrophotometer (UV) at 20°C and 90°C, respectively, with a test wavelength range of 250 to 2500nm). DETAILED DESCRIPTION

[0056] The following describes the implementation of the present invention through specific embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0057] It should be noted that, in the absence of conflict, the features in the following examples and embodiments can be combined with each other. It should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of the present invention. The test methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0058] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention.

[0059] The present invention is further described below by means of specific examples, but the present invention is not limited thereto, and the specific protection scope is shown in the claims.

[0060] Example 1

[0061] Preparation of vanadium dioxide powder

[0062] 13.5g of V2O5 was added to a beaker containing 400mL of deionized water. After the dispersion was heated to 75°C, 6.0g of hydrazine hydrate (40wt%) was slowly added dropwise to the dispersion under stirring. After the addition was completed, stirring was continued for 1h, and then the dispersion was transferred to a reactor and reacted at 260°C for 24h. After the reaction was completed, the mixture was centrifuged several times, and the centrifuged product was vacuum dried to obtain vanadium dioxide powder.

[0063] Preparation of trithioester-terminated polymers by reversible addition-fragmentation chain transfer (RAFT) polymerization

[0064]

[0065] 10.0 g N,N-dimethylacrylamide (DMA), 0.71 g S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT), and 0.05 g azobisisobutyronitrile (AIBN) were added to 30 mL 1,4-dioxane and completely dissolved. The system was stirred and reacted at 65°C for 18 h under nitrogen protection. The resulting solution was precipitated and washed in n-hexane, and the product was filtered off and dried in vacuum at 40°C to obtain trithioester-terminated poly(N,N-dimethylacrylamide) (PDMA-DOPAT) yellow powder.

[0066] Preparation of PDMA-SH Hydrophilic Polymer Capped with Thiol Group

[0067]

[0068] 3.0 g PDMA-DOPAT, 0.539 g n-hexylamine and 0.065 g tributylphosphine were added to 5 mL tetrahydrofuran, and the mixture was stirred at 30 °C for 6 h under nitrogen protection. After the reaction, the solution was added dropwise into n-hexane for precipitation and washed three times. The upper precipitate was collected by filtration and dried in vacuo at 40 °C to obtain PDMA-SH white powder.

[0069] Preparation of VO2@KH-570 nanopowder

[0070] 1.0g VO2 nanopowder was ultrasonically dispersed in 100mL anhydrous ethanol for 30min, ammonia was slowly added to adjust the pH to 10, 0.05g γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) was added, and then the system was heated to 60℃ for 6h. After the reaction, the unreacted KH-570 was removed by centrifugation and washed with anhydrous ethanol several times, and the solid product after centrifugation was dried in a vacuum oven at 40℃ to obtain VO2@KH-570 nanopowder.

[0071] Preparation of VO2@PDMA nanoparticles

[0072] 0.50 g of VO2@KH-570 nanopowder obtained in Example 4 was dispersed in 20 mL of tetrahydrofuran by ultrasonication for 30 min, and then 0.50 g of PDMA-SH was added and fully dissolved, and then 0.02 g of AIBN was added and reacted at 60°C under nitrogen protection for 24 h. After the reaction was completed, it was centrifuged and washed twice with tetrahydrofuran, and finally the washed product was vacuum dried at 60°C for 24 h to obtain VO2@PDMA nanoparticles.

[0073] Example 2

[0074] Preparation of vanadium dioxide powder

[0075] 10.0g of V2O5 was added to a beaker containing 300mL of deionized water. After the dispersion was heated to 75°C, 5.5g of hydrazine hydrate (40wt%) was slowly added dropwise to the dispersion under stirring. After the addition was completed, stirring was continued for 1h, and then the dispersion was transferred to a reactor and reacted at 280°C for 24h. After the reaction was completed, the mixture was centrifuged several times, and the centrifuged product was vacuum dried to obtain vanadium dioxide powder.

[0076] Preparation of trithioester-terminated polymers by reversible addition-fragmentation chain transfer (RAFT) polymerization

[0077] 10.0 g N,N-dimethylacrylamide (DMA), 0.55 g S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT), and 0.04 g azobisisobutyronitrile (AIBN) were added to 30 mL 1,4-dioxane and completely dissolved. The system was stirred and reacted at 65°C for 18 h under nitrogen protection. The resulting solution was precipitated and washed in n-hexane, and the product was filtered off and dried in vacuum at 40°C to obtain trithioester-terminated poly(N,N-dimethylacrylamide) (PDMA-DOPAT) yellow powder.

[0078] Preparation of PDMA-SH Hydrophilic Polymer Capped with Thiol Group

[0079] 3.0 g PDMA-DOPAT, 0.42 g n-hexylamine and 0.05 g tributylphosphine were added to 5 mL tetrahydrofuran, and the mixture was stirred at 30 °C for 6 h under nitrogen protection. After the reaction, the solution was added dropwise into n-hexane for precipitation and washed three times. The upper precipitate was collected by filtration and dried in vacuo at 40 °C to obtain PDMA-SH white powder.

[0080] Preparation of VO2@KH-570 nanoparticles

[0081] 1.0g VO2 nanopowder was ultrasonically dispersed in 80mL anhydrous ethanol for 30min, ammonia was slowly added to adjust the pH to 10, 0.07g γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) was added, and then the system was heated to 60℃ for 6h. After the reaction, the unreacted KH-570 was removed by centrifugation and washed with anhydrous ethanol several times, and the solid product after centrifugation was dried in a vacuum oven at 40℃ to obtain VO2@KH-570 nanopowder.

[0082] Preparation of VO2@PDMA nanoparticles

[0083] 0.50g VO2@KH-570 nanopowder was dispersed in 30mL tetrahydrofuran by ultrasonication for 30min, then 0.3g PDMA-SH was added and fully dissolved, and then 0.015g AIBN was added and reacted at 70℃ under nitrogen protection for 14h. After the reaction was completed, it was centrifuged and washed twice with tetrahydrofuran, and finally the washed product was vacuum dried at 60℃ for 24h to obtain VO2@PDMA nanoparticles.

[0084] Example 3

[0085] Preparation of vanadium dioxide powder

[0086] 12.5g of V2O5 was added to a beaker containing 350mL of deionized water. After the dispersion was heated to 75°C, 5.8g of hydrazine hydrate (40wt%) was slowly added dropwise to the dispersion under stirring. After the addition was completed, stirring was continued for 1h, and then the dispersion was transferred to a reactor and reacted at 280°C for 20h. After the reaction was completed, the mixture was centrifuged several times, and the centrifuged product was vacuum dried to obtain vanadium dioxide powder.

[0087] Preparation of trithioester-terminated polymers by reversible addition-fragmentation chain transfer (RAFT) polymerization

[0088] 11.5 g N,N-dimethylacrylamide (DMA), 0.45 g S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT), and 0.03 g azobisisobutyronitrile (AIBN) were added to 30 mL 1,4-dioxane and completely dissolved. The system was stirred and reacted at 65°C for 18 h under nitrogen protection. The resulting solution was precipitated and washed in n-hexane, and the product was filtered off and dried in vacuum at 40°C to obtain trithioester-terminated poly(N,N-dimethylacrylamide) (PDMA-DOPAT) yellow powder.

[0089] Preparation of PDMA-SH Hydrophilic Polymer Capped with Thiol Group

[0090] 5.2 g PDMA-DOPAT, 0.75 g n-hexylamine and 0.1 g tributylphosphine were added to 5 mL tetrahydrofuran, and the mixture was stirred at 30 °C for 6 h under nitrogen protection. After the reaction, the solution was added dropwise into n-hexane for precipitation and washed three times. The upper precipitate was collected by filtration and dried in vacuo at 40 °C to obtain PDMA-SH white powder.

[0091] Preparation of VO2@KH-570 nanoparticles

[0092] 1.5 g of VO2 nanopowder was ultrasonically dispersed in 120 mL of anhydrous ethanol for 30 min, ammonia was slowly added to adjust the pH to 10, 0.09 g of γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) was added, and then the system was heated to 60 ° C for 6 h. After the reaction, the unreacted KH-570 was removed by centrifugation and washed with anhydrous ethanol several times, and the solid product after centrifugation was dried in a vacuum oven at 40 ° C to obtain VO2@KH-570 nanopowder.

[0093] Preparation of VO2@PDMA nanoparticles

[0094] 0.50g VO2@KH-570 nanopowder was dispersed in 50mL tetrahydrofuran by ultrasonication for 30min, then 0.4g PDMA-SH was added and fully dissolved, and then 0.025g AIBN was added and reacted at 65℃ under nitrogen protection for 18h. After the reaction was completed, it was centrifuged and washed twice with tetrahydrofuran, and finally the washed product was vacuum dried at 60℃ for 24h to obtain VO2@PDMA nanoparticles.

[0095] Application Example 1

[0096] Disperse 1g of VO2 powder obtained in Example 2 evenly in 99mL of water solvent, use a cell crusher to ultrasonicate for 30min until the powder is evenly dispersed to prepare a VO2-based slurry. Take 7.5g of water-based polyurethane resin (model: Shengbang 9080) in a 20mL beaker, take 5g of the above slurry in a 10mL serum bottle, slowly add it dropwise to the water-based resin and stir until it is evenly dispersed. Weigh 2.5g of film-forming aid, 0.3g of leveling agent, and 0.3g of defoaming agent in a 10mL serum bottle, mix evenly, and slowly add it dropwise to the beaker. After fully stirring, VO2-based intelligent thermal insulation coating is obtained.

[0097] Application Example 2

[0098] Disperse 1g of VO2@KH-570 nanopowder obtained in Example 3 evenly in 99mL of water solvent, use a cell crusher to ultrasonicate for 30min until the powder is evenly dispersed to prepare a VO2@KH-570-based slurry. Take 7.5g of waterborne polyurethane resin (model: Shengbang 9080) in a 20mL beaker, take 5g of the above slurry in a 10mL serum bottle, slowly add it dropwise to the waterborne resin and stir until it is evenly dispersed. Weigh 2.5g of film-forming aid, 0.3g of leveling agent, and 0.3g of defoaming agent in a 10mL serum bottle, mix evenly, and slowly add it dropwise to the beaker. After fully stirring, VO2@KH-570-based intelligent thermal insulation coating is obtained.

[0099] Application Example 3

[0100] Preparation of VO2@PDMA nanoparticle-based highly weather-resistant water-based intelligent thermal insulation coating

[0101] Disperse 1g of VO2@PDMA nanoparticles prepared in Example 1 evenly in 99mL of water solvent, use a cell crusher to ultrasonicate for 30min until the powder is evenly dispersed to prepare a VO2@PDMA-based slurry. Take 7.5g of water-based polyurethane resin (model: Shengbang 9080) in a 20mL beaker, take 5g of the above slurry in a 10mL serum bottle, slowly add it dropwise to the water-based resin and stir until it is evenly dispersed. Weigh 2.5g of film-forming aid, 0.3g of leveling agent, and 0.3g of defoaming agent in a 10mL serum bottle, mix evenly, and slowly add it dropwise to the beaker. After fully stirring, VO2@PDMA-based smart thermal insulation coating is obtained.

[0102] Preparation of smart thermal insulation coating

[0103] 4 mL of the VO2@KH-570-based smart thermal insulation coating, VO2@KH-570-based smart thermal insulation coating, and VO2@PDMA-based smart thermal insulation coating prepared in Application Examples 1 to 3 were respectively taken and evenly coated on a glass substrate using a 50 μm thick wire rod by roller coating. The substrate was then quickly placed in a 60°C oven to accelerate solvent evaporation to obtain VO2-based smart thermal insulation coatings, VO2@KH570-based smart thermal insulation coatings, and VO2@PDMA-based smart thermal insulation coatings. After thorough drying, the dry film thickness was about 5 μm.

[0104] Performance Analysis

[0105] 1. Take the yellow powder of PDMA-DOPAT prepared in Example 1, dissolve it in deuterated acetone, and perform nuclear magnetic resonance spectroscopy test using AvanceIII HD 600MHz nuclear magnetic resonance instrument. The results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the characteristic peaks of PDMA polymer appear in the figure, among which 1.42~1.91ppm are attributed to the main chain -CH2-, 2.30~2.78ppm are attributed to the main chain -CH-, and 2.78~3.27ppm are attributed to the side chain -CH3. In addition, there are characteristic chemical shifts of RAFT chain transfer agent DOPAT in the spectrum (0.95ppm is attributed to the methyl group in the RAFT agent), indicating that the PDMA homopolymer product retains the functional group of DOPAT, and RAFT polymerization is successfully carried out to prepare PDMA homopolymer containing trithioester terminal functional groups.

[0106] 2. The yellow powder of PDMA-DOPAT and the white powder of PDMA-SH prepared in Example 1 were taken respectively, and tetrahydrofuran was used as solvent to prepare polymer solutions with a concentration of 0.001 g / mL. The ultraviolet absorption test was performed using a UV-3600 ultraviolet-visible-near infrared spectrophotometer. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the PDMA-DOPAT polymer before aminolysis has an ultraviolet absorption peak of the trithioester group at 308nm, which further verifies that the trithioester functional group of the DOPAT chain transfer agent is connected to the polymer chain segment. The ultraviolet absorption peak of the PDMA-SH polymer after the aminolysis reaction disappears at 308nm, that is, the terminal trithioester group disappears, indicating that the aminolysis reaction successfully converts the trithioester group to generate a thiol-terminated PDMA-SH polymer.

[0107] 3. The vanadium dioxide powder prepared in Example 1 was characterized by using a Gemini 300 scanning electron microscope. Figure 3As shown, it can be seen that the obtained vanadium dioxide powder has a small primary particle size (30-40 nm). Then, the vanadium dioxide powder, VO2@KH-570 nanopowder, and VO2@PDMA nanoparticles prepared in Example 1 were taken respectively, and the thermal weight loss of the samples was tested by TGA55 thermogravimetric analyzer in N2 atmosphere. The test temperature range was 30-700°C, and the heating rate was 20°C / min. The results are shown as follows: Figure 4 As shown, from Figure 4 It can be seen that the weight loss of the unmodified VO2 nanopowder reaches the maximum value (about 0.5%) at 270°C, and the mass remains unchanged as the temperature rises to 700°C, while the thermal weight loss of VO2@KH-570 nanopowder when heated to 700°C is about 1.4%, indicating that the silane coupling agent is successfully grafted to the surface of VO2 powder. The thermal weight loss of VO2@PDMA nanoparticles modified with PDMA polymer reaches the maximum value (2.5%) at 600°C. It can be seen that as the modification proceeds, the weight loss of the nanopowder gradually increases, indicating that the block polymer is successfully grafted to the powder surface.

[0108] 4. Take the vanadium dioxide powder and VO2@PDMA nanoparticles prepared in Example 1 respectively, and use SmartlabSE powder diffractometer to perform XRD test at room temperature. The test range is 10-80° and the test step is 1° / min. Observe the crystal changes of the two. The results are as follows: Figure 5 As shown, from Figure 5 It can be seen that the powders before and after modification are both in the monoclinic phase, indicating that the process of polymer modification of VO2 powder will not affect the crystal form and dimming performance of the powder.

[0109] 5. Take 0.1 g of vanadium dioxide powder and VO2@PDMA nanoparticles prepared in Example 1, respectively, disperse them in 8 mL of distilled water, and then ultrasonically disperse them in a cell crusher for 30 min. Let them stand and observe the sedimentation of the two. Figure 5 As shown, from Figure 6 It can be seen that the unmodified VO2 powder has already settled significantly after 5 days of standing, while the sedimentation rate of the hydrophilic polymer-modified VO2@PDMA nanoparticles has slowed down significantly, and after 7 days of standing, it still maintains a certain dispersion state without obvious sedimentation. This is mainly because the hydrophilic PDMA can present a stretched state in the aqueous solution system, improving the suspension effect of the powder in the aqueous phase. Based on the above results, PDMA as a shell material can improve the dispersibility of the powder in the aqueous phase.

[0110] 6. Figure 7(a) is a photo of the thermal insulation coatings obtained in Application Example 1, Application Example 2, and Application Example 3. It can be seen from the photo that they are all brown-yellow films with excellent light transmittance, and the surface of the film coating is uniform. The optical properties of the three different thermal insulation coatings were tested at 20°C and 90°C using an ultraviolet-visible-near infrared spectrophotometer (UV) with a test wavelength range of 250-2500nm. The results are shown in Figure 1. Figure 7 As shown in (b), it can be seen from the figure that the film has excellent solar modulation ability when tested at high temperature 90℃ and low temperature 20℃. The solar modulation ability ΔT of the VO2-based thin film coating of Application Example 1 is sol =8.47%, while the VO2@PDMA-based thin film coating of Application Example 3 exhibits a higher solar light modulation capability (ΔT sol =9.58%). This is mainly because the modification of PDMA polymer improves the dispersibility of inorganic powders and reduces the agglomeration of large powder particles. At the same time, the presence of the polymer shell is conducive to improving the compatibility of powders and organic resins and reducing interface defects. The above results prove that PDMA-modified VO2 can make nanoparticles exert better dimming performance and achieve efficient heat insulation effect.

[0111] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing VO2@PDMA nanoparticles, characterized in that: The following steps are involved: (1) Preparation of vanadium dioxide powder: Add V2O5 to deionized water, stir to form a dispersion, heat the dispersion and drop hydrazine hydrate under stirring, continue stirring to react after the dropwise addition is completed, then transfer the solution to a reactor to continue the reaction, perform post-treatment after the reaction is completed, and obtain vanadium dioxide powder; (2) Preparation of thiol-terminated PDMA-SH hydrophilic polymer: a) N,N-dimethylacrylamide, S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) and azobisisobutyronitrile were added to 1,4-dioxane solvent, and stirred to react under nitrogen protection after being completely dissolved. After the reaction was completed, the resulting solution was precipitated, washed and filtered in n-hexane. The resulting product was vacuum dried at 40-90° C. for 8-24 h to obtain trithioester-terminated poly(N,N-dimethylacrylamide), which was recorded as PDMA-DOPAT; b) adding the PDMA-DOPAT, n-hexylamine and tributylphosphine prepared in step a) into tetrahydrofuran, stirring and reacting under nitrogen protection, and after the reaction, dropping the solution into n-hexane for precipitation and washing, collecting the precipitate by filtration, and vacuum drying at 40-90° C. for 8-24 h to obtain a thiol-terminated PDMA-SH hydrophilic polymer; (3) Preparation of VO2@PDMA nanoparticles: The vanadium dioxide powder prepared in step (1) was ultrasonically dispersed in anhydrous ethanol, ammonia water was added to adjust the pH, γ-(methacryloyloxy)propyltrimethoxysilane was added, and the system was then heated for reaction. After the reaction, the system was centrifuged, washed with anhydrous ethanol, and vacuum dried at 40-70°C for 12-24h to obtain VO2@KH-570 nanopowder; The VO2@KH-570 nanopowder is ultra-dispersed in tetrahydrofuran, and then the PDMA-SH hydrophilic polymer prepared in step (2) is added and stirred until fully dissolved, and then the initiator AIBN is added, and then reacted under nitrogen protection. After the reaction is completed, centrifugation and tetrahydrofuran washing are performed, and the washed product is vacuum dried at 50-70°C for 12-24h to obtain VO2@PDMA nanoparticles.

2. The method according to claim 1, characterized in that It also includes one or more of the following technical features: In step (1), the mass ratio of V2O5 to hydrazine hydrate is (5-10): (1-5); In step (1), the reaction temperature in the reactor is 240-350° C., and the reaction time is 6-30 hours.

3. The method according to claim 1, characterized in that It also includes one or more of the following technical features: In step (2), the mass ratio of N,N-dimethylacrylamide and S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) in a) is (80-120):(5-15); In step (2), the mass ratio of S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) and azobisisobutyronitrile in a) is (15-50):(0.5-7); a) the mass ratio of 1,4-dioxane to N,N-dimethylacrylamide is (5-10):(0.5-5); b) The mass ratio of PDMA-DOPAT, n-hexylamine and tributylphosphine is (90-150):(10-30):(0.5-5).

4. The method according to claim 1, characterized in that It also includes one or more of the following technical features: In step (3), the mass ratio of vanadium dioxide powder to γ-(methacryloyloxy)propyltrimethoxysilane is (5-30): (0.5-3); In step (3), the mass ratio of VO2@KH-570 nanopowder to PDMA-SH hydrophilic polymer is (1-10): (0.2-2); In step (3), the mass ratio of VO2@KH-570 nanopowder to AIBN is (10-40):1; The reaction temperature under nitrogen protection in step (3) is 50-70° C., and the reaction time is 12-24 h.

5. VO2@PDMA nanoparticles prepared by the method according to any one of claims 1 to 4.

6. The intelligent thermal insulation coating prepared by using the VO2@PDMA nanoparticles according to claim 5, characterized in that: The preparation method includes: uniformly adding the aqueous dispersion of VO2@PDMA nanoparticles into the aqueous resin, stirring until uniformly dispersed, and obtaining a system dispersion; uniformly mixing a film-forming aid, a leveling agent, and a defoaming agent, and then adding them to the system dispersion, stirring evenly, and obtaining an intelligent thermal insulation coating.

7. The intelligent thermal insulation coating according to claim 6, characterized in that: The mass ratio of the water-based resin to the VO2@PDMA nanoparticle aqueous dispersion is (50-100): (40-60); the mass fraction of the VO2@PDMA nanoparticle aqueous dispersion is 1wt%.

8. The intelligent thermal insulation coating according to claim 6, characterized in that: The dropping speed of VO2@PDMA nanoparticle aqueous dispersion is 0.5~2mL / min.

Citation Information

Patent Citations

  • Waterproof vanadium dioxide intelligent temperature control coating and preparation method thereof

    CN113773707A

  • Polyacrylate polymer-vanadium dioxide microcapsule as well as preparation method and application thereof

    CN114367250A